2022
DOI: 10.1111/iej.13866
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the outcome of pulpotomy in permanent teeth

Abstract: The promotion of minimally invasive treatments focussed on the maintenance of pulp vitality has become a priority area in Endodontics. These vital pulp treatments (VPT) include partial and full pulpotomy, during which diseased coronal pulp tissue is removed prior to placement of a capping biomaterial and restoration. Traditionally, pulpotomies were confined to the treatment of carious primary and traumatized permanent teeth. However, these treatments have now been proposed as definitive solutions for cariously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 106 publications
1
17
0
Order By: Relevance
“…Conversely, Özgür et al (2017) found that the use of saline solution as irrigant for haemorrhage control was associated with a higher success rate in pulpotomies compared to sodium hypochlorite, although no statistical significance was detected. According to a recent review published by Duncan et al (2022), a variety of factors influence the outcome of pulpotomy in permanent teeth, including the type of capping material used, caries depth, pulp status, level of pulpal biomarkers and final restoration integrity. Other possible influencing factors include exposure type, periodontal condition, pulpal irrigation, magnification, operator experience, operating field isolation and type of pulpotomy, which require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Özgür et al (2017) found that the use of saline solution as irrigant for haemorrhage control was associated with a higher success rate in pulpotomies compared to sodium hypochlorite, although no statistical significance was detected. According to a recent review published by Duncan et al (2022), a variety of factors influence the outcome of pulpotomy in permanent teeth, including the type of capping material used, caries depth, pulp status, level of pulpal biomarkers and final restoration integrity. Other possible influencing factors include exposure type, periodontal condition, pulpal irrigation, magnification, operator experience, operating field isolation and type of pulpotomy, which require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Dentinal bridge formation after the pulpotomy procedure is considered to be a significant indicator of a favourable outcome of partial pulpotomy (Duncan et al, 2022; Leye Benoist et al, 2012; Nosrat & Nosrat, 1998). This is because it demonstrates that the pulp remains vital underneath the capping material.…”
Section: Discussionmentioning
confidence: 99%
“…Βy performing VPT in vital mature teeth, a great number of root canal therapies may be prevented, thus preserving pulp vitality and consequently the health of the tissue. Preservation of pulp vitality is of great importance, due to the maintenance of the defensive mechanism of the pulp tissue and the structural integrity of the tooth (Duncan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Such treatments hold various clinical and biological benefits, such as avoiding tooth loss, restoring tooth functions, and reversing/resisting the progress of diseased tooth condition, [ 3 ] but still result in a high percentage of failure in clinical practice. [ 4–6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Such treatments hold various clinical and biological benefits, such as avoiding tooth loss, restoring tooth functions, and reversing/resisting the progress of diseased tooth condition, [3] but still result in a high percentage of failure in clinical practice. [4][5][6] The regeneration of the dentin-pulp complex is mainly based on a new population of odontoblast-like cells derived from pulp stem cells in the healthy portion of the pulp, [7] making it essential to protect these progenitor cells and induce their activity. However, pulp exposure is usually accompanied by local accumulation of inflammation mediators, such as cytokines, chemokines, and oxidative stress markers (e.g., reactive oxygen intermediates), [8,9] which, at high concentrations, can cause oxidative damage to the cells.…”
Section: Introductionmentioning
confidence: 99%